Inadequate number of staff and other reasons for implicit rationing of nursing care across hospital types and units - Renáta Zeleníková; Darja Jarošová; Eva Mynaříková; Eva Janíková; Ilona Plevová (Wiley, 2023)
Abstract Aim The aim of the study was to find differences in perceived reasons for implicit rationing of nursing care across hospital types and units. Design A descriptive multicentre study. Methods The study in 14 Czech acute care hospitals was conducted from September 2019 to October 2020. The sample consisted of 8316 nurses working in medical and surgical units. Items for rating the reasons for implicit rationing of nursing care were selected from the MISSCARE Survey. Nurses were asked to rate each item on a scale from 0 (a not significant reason) to 10 (the most significant reason). Results The most significant reasons for implicit rationing of nursing care were 'Inadequate number of staff', 'Inadequate number of assistive personnel' and 'Unexpected patient admission and discharge'. Most reasons were rated as more significant by nurses from non‐university hospitals. Nurses from medical units perceived all reasons for implicit rationing of nursing care as more significant.